SREBPs as the potential target for solving the polypharmacy dilemma - Wang, Xue; Chen, Yanqiu; Meng, Heyu; Meng, Fanbo (Frontiers in Physiology, 2024)
The phenomenon of polypharmacy is a common occurrence among older people with multiple health conditions due to the rapid increase in population aging and the popularization of clinical guidelines. The prevalence of metabolic syndrome is growing quickly, representing a serious threat to both the public and the worldwide healthcare systems. In addition, it enhances the risk of cardiovascular disease as well as mortality and morbidity. Sterol regulatory element binding proteins (SREBPs) are basic helix-loop-helix leucine zipper transcription factors that transcriptionally modulate genes that regulate lipid biosynthesis and uptake, thereby serving an essential role in biological systems regulation. In this article, we have described the structure of SREBPs and explored their activation and regulation of signals. We also reveal that SREBPs are intricately involved in the modulation of metabolic diseases and thus have tremendous potential as the novel target for single-drug therapy for multiple diseases.